Risk management in the clinic – diagnostic laboratories - Sydorko, Ihor; Baitsar, Roman (Видавництво Львівської політехніки, 2020)
Adopting socially responsible management practices of the organization promotes greater awareness in decisionmaking, based on a better understanding of society’s expectations, anticipation of risks, and opportunities. Responsible management of an organization can improve its relationships with stakeholders. Encouraging compliance with regulatory obligations leads to decisions that are more likely to gain the support and trust of those who implement them and who they influence. The result can be improved risk management practices and improved reputation. The concept of “risk” today has a fairly broad meaning and is used in completely different contexts. Synonyms of risk can be such concepts as “danger”, “threat”, “trouble”, etc. However, in many definitions of risk in the scientific literature, this term is used in a special sense, where risk is associated primarily with the concept of uncertainty. Therefore, the risk is understood as uncertainty, which can result in one or another adverse event. Clinical risks – risks that arise directly from the provision of medical care. These include clinical errors and negligence, infections in medical care, and non-consent. The principles of risk management and the need to use them are effectively applied in many areas of economic activity and public administration, including health care, as well as institutions that provide regulatory activities in these areas, including clinical diagnostic laboratories. Today, prevention as management of patient quality of health has become a dominant part of medicine, where laboratory diagnostics, which can detect the risks of many diseases, is not the least important. The presence in the health care system of only certain fragments of activity risk necessitates the formation of an overwhelming majority of an effective integrated risk management system, which must comply with certain requirements and principles: determining the characteristics of the system; optimization of the risk management model of medical structures; substantiation of prerequisites for the introduction of a comprehensive medical risk management system and evaluation of the effectiveness of its operation.
Keywords: Risk management; Laboratory medicine; Medical errors; Laboratory diagnostics; Regulatory support; Quality control; and Evaluation